Functional regimes define soil microbiome response to environmental change - Kiseok Keith Lee; Siqi Liu; Kyle Crocker; Jocelyn Wang; David R. Huggins; Mikhail Tikhonov; Madhav Mani; Seppe Kuehn (Nature, 2025)
Abstract The metabolic activity of soil microbiomes has a central role in global nutrient cycles 1 . Understanding how soil metabolic activity responds to climate-driven environmental perturbations is a key challenge 2,3 . However, the ecological, spatial and chemical complexity of soils 4–6 impedes understanding how these communities respond to perturbations. Here we address this complexity by combining dynamic measurements of respiratory nitrate metabolism 7 with modelling to reveal functional regimes that define soil responses to environmental change. Measurements across more than 1,500 soil microcosms subjected to pH perturbations 8,9 reveal regimes in which distinct mechanisms govern metabolite dynamics. A minimal model with two parameters, biomass activity and growth-limiting nutrient availability, predicts nitrate utilization dynamics across soils and pH perturbations. Parameter shifts under perturbation reveal three functional regimes, each linked to distinct mechanisms: (1) an acidic regime marked by cell death and suppressed metabolism; (2) a nutrient-limited regime in which dominant taxa exploit matrix-released nutrients; and (3) a resurgent growth regime driven by exponential growth of rare taxa in nutrient-rich conditions. We validated these model-derived mechanisms with nutrient measurements, amendment experiments, sequencing and isolate studies. Additional experiments and meta-analyses suggest that functional regimes are widespread in pH-perturbed soils.